A SURVEY STUDY ON STUDENTS’ PERCEPTION OF TEACHERS’ ONLINE TEACHING DURING STUDY FROM HOME POLICY IN JAYAPURA - Herry Wahyudi Susanto (Language-Edu, 2021)
The pandemic that came in 2019 has ruined learning process forced students living in the with less support territory to drop their school. Even though virtual teaching had been declared from the very beginning to overcome and compensate the pandemic situation, the readiness to adapt the urgent sudden shift become a major issues worldwide, especially to the less support area such as Jayapura. Under this clutter, teachers play an important role to selectively determine the most proper and utilizable media that fits the students’ situation. Therefore, this study was aimed to investigate teachers’ wisdom in Jayapura in terms of media selection, their perfomance using the media, and students’ challenge due to using the. A descriptive quantitative survey research method was applied by assinging 5 questionnaire items adopted from Technology Acceptance Model to 123 students. The data found that students in remote area faced less trouble than students in urban area due to the teachers’ wisdom to select the most proper and applicable teaching media requiring less quota according to the limited circumtance in remote area.